Correlation of serum homocysteine with HbA1c and kidney function in type 2 diabetic patients: insights from estimated glomerular filtration rate and renal impairment - Kumar, Vineet; Gulati, Yuvraj; Giri, Richa; Babulal, Verma Rajendra Kumar; Varma, Punit; Kala, Chayanika (International Journal of Research in Medical Sciences, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a prevalent metabolic disorder associated with complications, particularly diabetic nephropathy (DN), a major cause of end-stage renal disease (ESRD). Early detection of DN is essential to prevent progression. Serum homocysteine (Hcy), a marker linked to oxidative stress and endothelial dysfunction, has shown potential in predicting vascular and renal complications. However, its relationship with glycemic control (HbA1c) and kidney function (eGFR) remains underexplored. This study examines these correlations in T2DM patients. Methods: This cross-sectional study included 156 T2DM patients recruited from G.S.V.M. medical college, Kanpur (January 2023-April 2024). Serum Hcy, HbA1c, and eGFR were measured using standardized techniques. Pearson and Spearman correlations, along with multiple linear regression, were used to evaluate relationships while adjusting for confounders like age, diabetes duration, and lipid profile. Results: Serum Hcy levels demonstrated a significant positive correlation with HbA1c (r=0.47, p<0.01), indicating an association with poorer glycemic control. Additionally, a negative correlation was observed between serum Hcy and eGFR (r=-0.52, p<0.001), suggesting that elevated homocysteine levels were associated with declining kidney function. These correlations remained significant after adjustments for confounders. Conclusions: Elevated serum homocysteine is strongly associated with higher HbA1c and lower eGFR, suggesting its potential as a biomarker for glycemic control and renal impairment in T2DM. Routine homocysteine measurement could aid early DN detection and management. Further studies are needed to validate these findings.